An examination of the organizational culture at the policing - Elekes , Edit (Applied Studies in Agribusiness and Commerce, 2014)
The subject of this thesis is presentation of the examination related to the organizational culture of the Police, the special law enforcement body which guarantees internal order and public security. The police, at the same time, as armed law enforcement body ensure the order of the economy and its legal security. Security is not only important for the citizens and social organizations, but also for the profit and non-profit organizations. The Police carry out official work, but also provide services that presuppose two types of contact system and modes of management. There were a number of changes in the body of the Police over the past two decades (e.g. accession to the EU, accession to the Schengen area, integration of the Police and the Border Guards, outsourcing certain activities, regionalization of sponsorship activities), in which I have taken part as a manager of the developmental programs. These changes have not only affected the police organization and the approach of the employees, but also the organizational culture. The changes cannot be considered as closed: the Ministry of Interior, governing the Police, takes decisions on organizational changes, but also the managers at the Police play an important role in this process. Under „change” I do not necessarily understand a change in the structure, but also a change in the organizational culture to create support for the reform process, and the option to co-ordinate the diverse structures. The changes have obviously affected the thinking of the managers and the employees, as well as their relationship to the organization. The official duties, including the detection of the crimes (including agricultural and economic crimes), cannot be performed without the day-today cooperation with the bodies of the civil law enforcement, through which the Police may increase the effectiveness of detection of such crimes and thus the citizens’ subjective feeling of security. Therefore, the present thesis aims at the examination of the Police’s organizational culture and its management methods.